Comparison and application of different elasto-plastic constitutive models in FEM analysis of an excavated soil slope - Zhang, Kunyong; Ai, Yingbo (Journal of Civil Engineering and Management, 2012)
A modified anisotropic elasto-plastic model is presented in this paper based on the frame work of Modified Cam-clay model and Original Sekiguchi-Ohta model by applying a new stress ratio parameter, through which the yield locus and hardening axis in the p-q plane were adjusted to give a more reasonable description of the practical excavation stress path from initial K0 state. Typical excavated soil slope was selected as the illustration example to carry out the finite element numerical analysis by applying four constitutive models (Original Cam-Clay, Modified Cam-Clay, Original Sekiguchi-Ohta and Modified Sekiguchi-Ohta). The calculated displacements of the slope with above different constitutive models were then compared with the measured infield data. It was found the field measured data agree better with the results calculated from modified model, which indicates that the modified anisotropic model is more suitable in the description of the stress path of excavated soils slope after K0 consolidation.